Analisis Geometri Peledakan Untuk Mendapatkan Hasil Fragmentasi dan Digging Time Optimal di Pit North Tutupan PT. SIS site Adaro (PT. Adaro Indonesia) - Ahmad Erlangga Adji; M Bambang Soegeng; A Silvan Erusani (Jurnal Inovasi Pertambangan dan Lingkungan, 2021)
Blasting activity is really important thing to support production achievement in mine. Especially on drilling and blasting production. Good drilling also will affect the fragmentation outcome. Geometry applications have to conductbased on rock characteristics in every blasting location. In this case, correlation between burden and spacing in blasting geometry, how powder factor impact to fragmentation and also digging time excavator. The impact of change geometry blasting will result the appropriate digging time from fragmentation. PT. SIS digging time target is 12 seconds for all different classes of excavators. Hence, it is expected that the acquisition of digging time is reached. Thus, the production process will be influenced.Keywords - Geometry, Fragmentation, and Digging Time